2019
DOI: 10.1002/ange.201902839
|View full text |Cite
|
Sign up to set email alerts
|

Large Second Harmonic Generation (SHG) Effect and High Laser‐Induced Damage Threshold (LIDT) Observed Coexisting in Gallium Selenide

Abstract: A big challenge for nonlinear optical (NLO) materials is the application in high power lasers, which needs the simultaneous occurrence of large second harmonic generation (SHG) and high laser induced damage threshold (LIDT). Herein we report the preparation of a new Ga2Se3 phase, which shows the SHG intensities of around 2.3 times and the LIDT of around 16.7 times those of AgGaS2 (AGS), respectively. In addition, its IR transparent window ca. 0.59–25 μm is also significantly wider than that of AGS (ca. 0.48–≈1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…We measured the laser damage threshold of I with samples in the particle size of 150-212 μm by a solid-state laser (1064 nm, 10 ns, 1 Hz) with AgGaS 2 as the reference. 3 The measured laser damage threshold value of I was 144.4 MW cm −2 , which is about 65 times larger than that of the reference AgGaS 2 (2.2 MW cm −2 ).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We measured the laser damage threshold of I with samples in the particle size of 150-212 μm by a solid-state laser (1064 nm, 10 ns, 1 Hz) with AgGaS 2 as the reference. 3 The measured laser damage threshold value of I was 144.4 MW cm −2 , which is about 65 times larger than that of the reference AgGaS 2 (2.2 MW cm −2 ).…”
Section: Resultsmentioning
confidence: 76%
“…Nonlinear optical (NLO) crystals [1][2][3] are vital materials for portable all solid-state laser devices, which have been widely applied in modern laser micromachining, resource exploration, and laser communication. 4 Secondharmonic generation (SHG) response is the most important criteria for a superior NLO crystal.…”
Section: Introductionmentioning
confidence: 99%
“…The Kleinman symmetry was not assumed throughout this work, because it is not rigorously correct in some cases. [22][23][24]38 The calculated results are given in Table 2.…”
Section: Shg Coefficientsmentioning
confidence: 99%
“…However, it has been reported that the Kleinman symmetry is not rigorously correct in several cases. [22][23][24]38 Thus, it is of interest to probe the validity of the Kleinman symmetry, as well as the factors inuencing it, by studying the SHG responses of P-KDP and F-KDP.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic SHG efficiency of a material is primarily caused by NLO-active functional motifs with noncentrosymmetric (NCS) assembly; therefore, the exploration of new NLO-active motifs is important in finding new and promising NLO materials. Design strategies of IR NLO materials based on typical tetrahedral NLO-active motifs MQ 4 (M = IIB, III, IV metals; Q = S, Se), such as mixing different tetrahedral motifs in Na 2 M II M IV 2 Q 6 , (M II , M IV :IIB, IV metals; Q: chalcogen), inducing polarizability-favorable orientation of tetrahedral motifs in AZn 4 Ga 5 S 12 (A = K, Rb, Cs) and A 2 Ge 4 Se 10 (A = Rb, Cs), , and building supertetrahedral clusters in [ABa 2 Cl]­[Ga 4 S 8 ] (A = Rb, Cs) and NaIn 3 Se 5 , have progressed considerably. However, nontetrahedral NLO functional motifs, such as [HgSe 3 ] 4– and [HgSe 2 ] 2– in BaHgSe 2 and [BS 3 ] 3– in BaB 2 S 4 , are rarely explored. , …”
Section: Introductionmentioning
confidence: 99%